A JOURNEY THROUGH CREATIVITY AND UNORTHODOX LITERARY CRITICISM: LESSONS FROM THE MASSES OFFERING CRITICISM IN A VERNACULAR LANGUAGE IN KENYA (The University of Nairobi Journal of Language and Linguistics, 2023)
I cannot boast of being a literary critic of any shade – neither am I well tutoredin the literary world – but I read and enjoy literature and have incorporatedothers into my reading world. I, therefore, feel greatly humbled standing infront of this grand gathering of academic and language greats to express mybrief and non-academic wandering into the world of literature. Being alinguist, what I present here today is not an academic treatise on literarycriticism and creativity but thoughts, recollections and experiences I have hadin my dalliance with literature.Allow me to digress. In March 2000, the first 24-hour wholly vernacularstation in Kenya opened its doors. It was, and still is, known as Kameme FM.Being a lover and an ardent advocate of the use of vernacular languages, Ifrequently tuned into the station and was elated. I promptly wrote anapplication (in Gikuyu) requesting to be given time to air an academicprogramme which I christened “Book Review” in the application. The objectiveof the programme would be to “read” and “review” literature books in Gikuyu.Since there were not many books written in that language, I proposed to “readand translate books written in English and Kiswahili into Gikuyu” in keepingwith the station’s goal of broadcasting in Gikuyu. I had in mind a programmealong the lines of “Books and Bookmen”, which I had tuned in to for quite someyears. At that time, the programme was presented by now Professor EgaraKabaji of Masinde Muliro University and, among its pioneer participants,Professor Chris Wanjala of the Department of Literature at the University ofNairobi.But I did not have the intention of having a replica of Kabaji’s programme.I had thought of ways of making the programme interactive and I was lucky,given the current advancements in communication technology. I did not wantto lecture as Kabaji did. My intention was to go through the book as writtenand then give listeners a chance to call in and give a critique, howeveruneducated the response would be. I intended to start with a review of schoolset books on offer then. When the then station’s owner – Ms Rose Kimotho –  heard about my idea, she liked it. The station was in the process of looking fornew and fresh programmes and talents and she thought my proposal soundedunique and fresh. But there was skepticism all over: how could one possiblyreview English books in Gikuyu? All the same, some had some sort of faith in“this young university lecturer … maybe he has a way of doing it.”